The Investigation of the Water Splitting Activities of Coprecipitated Doped Nanotitania Powders - Gözel, Gözde; Çiftçioğlu, Muhsin (Izmir Institute of Technology, 2018)
The increase in the extent of greenhouse gases in earth’s atmosphere lies behind the global warming and climate change. The extensive use of unsustainable fossil fuels have intensified the greenhouse effect, causing global warming. Hydrogen is considered as an ideal fuel for the future. Hydrogen fuel can be produced from renewable energy sources and its life cycle is clean. Artificial photosynthesis has been considered as a promising prospect for the synthesis of renewable and sustainable fuels. Photocatalysis is expected to make a great contribution to environmental problems and renewable energy generation in the very near future. Titania based photocatalytic materials are one of the widely used materials in artificial photosynthesis research due to their unique chemical and optical properties. Photocatalytic water-splitting by using TiO2 based photocatalysts for hydrogen production offers a promising alternative for clean, low-cost and environmentally friendly production of hydrogen. ZrO2 doped TiO2 photocatalyst powders were prepared by coprecipitation and characterized in this work. The photocatalytic water splitting activities of these ZrO2 doped TiO2 photocatalyst powders in hydrogen production was investigated under UVVis light. The phase structures of the powders were significantly affected by the level of dopants and the primary particle sizes increased from about 130 nm to about 500 nm during heat treatments in the 550-700°C range. Maximum hydrogen yield of about 5000 μmol/hr gcat. was obtained with the 550°C heat treated powder doped at 0.1-0.1 mol% ZrO2-Nd2O3 level. ZrO2 doping above 10 mol% decreased the hydrogen yields of the catalysts to lower than 1000 μmol/hr gcat.

Küresel ısınma ve iklim değişikliğinin altında yatan ana neden atmosferdeki sera gazlarının artışıdır. Sürdürülemez fosil yakıtların geniş çaplı kullanımı sera gazı efektini arttırmakta, küresel ısınmaya sebep olmaktadır. Hidrojen gelecek için ideal yakıt olarak düşünülmektedir. Hidrojen yakıtı temiz ve yenilenebilir enerji kaynaklarından üretilebilirse temiz ve yenilenebilir bir döngüye sahiptir. Yapay fotosentez yenilenebilir ve sürdürülebilir yakıtlar için umut verici bir yaklaşım olarak düşünülmektedir. Fotokatalizin çevresel problemlere ve yenilenebilir enerji üretimine büyük katkıda bulunacağı umulmaktadır. Titanya esaslı fotokatalitik materyaller eşsiz kimyasal ve optik özelliklerinden dolayı yapay fotosentez araştırmalarında geniş çaplı olarak kullanılan materyal gruplarından biridir. Hidrojen üretimi için TiO2 kullanarak fotokatalitik su parçalama, temiz, düşük maliyetli ve çevre dostu hidrojen üretimi için umut verici bir alternatif sunmaktadır. Bu çalışmada, ZrO2 katkılı TiO2 fotokatalitik tozlar birlikte çöktürme ile hazırlandı ve karakterize edildi. Bu ZrO2 katkılı TiO2 fotokatalitik tozların UV görünür ışık altında hidrojen üretimindeki fotokatalitik su parçalama aktiviteleri belirlendi. Tozların faz yapıları, katkıların seviyeleri tarafından etkilendi ve 550-700°C aralığındaki ısıl işlem boyunca birincil parçacık boyutları yaklaşık 130 nm’den 500 nm’ye kadar arttı. Maksimum hidrojen verimi, 0.1-0.1mol% ZrO2-Nd2O3 seviyesinde katkılanan 550°C’de ısıl işlem gören tozda yaklaşık 5000 μmol/hr gcat olarak elde edildi. 10 mol%’nin üstünde ZrO2 katkılı katalizörlerin hidrojen verimleri 1000 μmol/hr gcat’den düşük bulundu.
Birlikte Çöktürülmüş Katkılı Nanotitanya Tozlarının Su Parçalama Aktivitelerinin İncelenmesi
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2018
Includes bibliographical references (leaves: 62-65)
Text in English; Abstract: Turkish and English
Keywords: Nanotitania powders; Titanium dioxide; Photocatalytic water splitting; Greenhouse effect